2000
DOI: 10.1095/biolreprod62.3.775
|View full text |Cite
|
Sign up to set email alerts
|

Meiosis-Activating Sterol-Mediated Resumption of Meiosis in Mouse Oocytes In Vitro Is Influenced by Protein Synthesis Inhibition and Cholera Toxin1

Abstract: To explore the possible signaling pathways of meiosis-activating sterol (MAS)-induced oocyte maturation and to elucidate whether the MAS pathway involves transcription or translation, arrested immature mouse oocytes were cultured with either the protein synthesis inhibitor cycloheximide or the heteronuclear RNA inhibitors alpha-amanitin or actinomycin D, respectively. Moreover, the possible involvement of a G protein-coupled receptor mechanism in MAS-mediated oocyte maturation was explored by influencing oocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…However, a follicle fluid sterol (called FF-MAS) was identified in a screen for the substances able to induce maturation of mouse follicle-enclosed oocytes (Byskov et al, 1995). Detailed analysis of cell signaling pathways comparing spontaneous and FF-MAS-induced maturation indicated that the pathways differ significantly between these mechanisms (Grondahl et al, 2000;Faerge et al, 2001). It is of interest that starfish oocytes of a number of species exhibit a significant degree of spontaneous maturation when dissected form the ovary, up to 10 -15% GVBD in the first 90 min (Schuetz, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…However, a follicle fluid sterol (called FF-MAS) was identified in a screen for the substances able to induce maturation of mouse follicle-enclosed oocytes (Byskov et al, 1995). Detailed analysis of cell signaling pathways comparing spontaneous and FF-MAS-induced maturation indicated that the pathways differ significantly between these mechanisms (Grondahl et al, 2000;Faerge et al, 2001). It is of interest that starfish oocytes of a number of species exhibit a significant degree of spontaneous maturation when dissected form the ovary, up to 10 -15% GVBD in the first 90 min (Schuetz, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Oocyte maturational competence is linked to follicle size and the follicular microenvironment immediately before nuclear and cytoplasmic maturation. Just as has been recorded for IVG, there is a clear need to optimise IVM culture media (Filali et al 2008) and to test the efficacy of physiologically relevant additives such as human chorionic gonadotrophin (Ge et al 2008); umbilical cord blood (Zhang et al 2007);and FCS (van Wagtendonk-de Leeuw et al 2000); as well as to test the efficacy of physiologically relevant additives such as follicular fluid meiosis activating sterol (Gröndahl et al 2000a(Gröndahl et al , 2000b and fetuin (Schroeder et al 1990, Dell'Aquila et al 1999; and to standardise factors such as priming with FSH, time of aspiration and the time interval to maturation in vitro (Mikkelsen et al 2000). There is evidence that meiotic maturation and fertilisation rates and blastocyst production are compromised when compared with in vivo matured counterparts (Banwell & Thompson 2008).…”
Section: The Ivm Of Oocytesmentioning
confidence: 99%
“…Follicular-Fluid Meiosis Activating Sterol (FF-MAS) which is found in high concentrations (around 1.6 µM) in follicular fluid in mammals [8], has been shown to be involved in the control of meiosis [8][9][10]. In mouse oocytes, addition of FF-MAS to the culture medium induce dosedependent resumption of meiosis [10][11], and increase the synchrony of cytoplasmic and nuclear maturation [12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In mouse oocytes, addition of FF-MAS to the culture medium induce dosedependent resumption of meiosis [10][11], and increase the synchrony of cytoplasmic and nuclear maturation [12][13].…”
Section: Introductionmentioning
confidence: 99%